RISK FACTORS, CLINICAL PROFILE, AND MANAGEMENT OF PATIENTS PRESENTING WITH EPISTAXIS: A CROSS-SECTIONAL STUDY - KARAMBELKAR, RAJESH A; JOSHI, SHREYAS S; BIRAJDAR, SANTOSH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To analyze risk factors, clinical profile, and management strategies for patients presenting with epistaxis. Methods: This was a cross-sectional study that was undertaken in the department of otorhinolaryngology at a tertiary care medical college. 60 adult patients presenting with epistaxis were included in this study. Demographic details, such as age and gender, were noted. Patients were evaluated for the presence of risk factors such as hypertension, bleeding disorder, or clotting defects. The clinical presentation of patients was also studied. Patients were managed as per standard protocol. Statistical analysis was done using SSPS 21.0 software, and p<0.05 was taken as statistically significant. Results: There were 44 males (73.33%) and 16 females (26.67%) with a M: F ratio of 1:0.36. The mean age of male and female patients was found to be 63.48±16.18 and 58.46±13.24, respectively. Assault or road traffic accidents, which were seen in 15 (25.00%) patients. The other common causes included hypertension (18.33%), nose picking (15%), and medication (such as antiplatelet or anticoagulant drugs)-induced (10%). Out of 60 patients, the majority (60.00%) were stable hemodynamically. 11 (18.33%) patients were found to have elevated blood pressure in addition to epistaxis. 5 (11.67%) patients were in hypotension, and hence fluid resuscitation was required. In 2 (3.33%) patients, the airway needed to be secured because of a compromised airway. The majority of the patients (75.00%) responded well to conservative measures. Posterior nasal packing (in addition to anterior nasal packing), cauterization, closed reduction of facial fractures, surgery for nasal mass, and functional endoscopic sinus surgery in remaining patients. Conclusion: Facial trauma, hypertension, and nose picking were the most common cases of epistaxis. Majority of the patients were hemodynamically stable and could be treated conservatively with measures such as medical management and anterior nasal packing.